Cephalometric changes produced by Planas and Bionator tracks in class II division 1 (Revista Nacional de Odontología, 2019)
Introduction: The Bionator and flat tracks are functional appliances that are among the treatment options forclass II malocclusion division 1. Objective: To compare the craniofacial and soft tissue changes resulting from orthopedic treatment to correct the class II division 1 malocclusion. Methods: an almost experimental intervention study was carried out; the sample unit was 622 children between 6 and 9 years of age, of both sexes, of the Guerrillero Heroico Primary School, area II of the Cienfuegos municipality; Of these, 20 patients were selected, divided into two groups equally, with which the functional appliances of Pistas Planas and Bionator were used as therapy. Lateral cephalograms of the skull were taken at the beginning and after one year of treatment; linear and angular measurements were performed by Steiner, Ricketts and McNamara. Cephalometric changes in skeletal and soft tissues were evaluated before and after treatment. Results: Changes were observed in measurements of lateral cranial radiographs, with cephalometric craniofa cial variations of significant statistical significance. In the soft tissues, the nasolabial angle increased, whichwas diminished due to the labial component, since there was light protrusion of the upper lip. Conclusion: it was statistically proven that patients with flat tracks had statistically more significant craniofacial changes in most cephalometric measurements; soft tissue changes were not significant for any of the two therapies employed, and the biotype was positively modified with both devices.
Keywords: malocclusion; activating appliances; functional orthodontic appliances; Bionator; Flat Tracks